2019
DOI: 10.2478/ssa-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Morphological diversity of chernozemic soils in south-western Poland

Abstract: Diverse chernozemic soils featured by thick mollic horizon, rich in humus, dark-coloured, structural, and saturated with base cations are relatively common in the loess-belt of SW Poland. It is postulated, that most of these soils may have similar initial (chernozemic) history of thick humus horizon, related to climate conditions and vegetation in the Late Pleistocene and the Neolithic periods. However, these soils exist on various bedrocks and under different moisture conditions that led to the development ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…This result suggests possible influences from the other physicochemical soil components important for pedogenic processes, such as carbonates and clay minerals [39]. However, the placement of some samples indicated the soil transformation (analyzed as the change from the bottom towards topsoil layers of the buried soil) from Chernozem through Phaeozem towards Luvisol (kurgan K3) and from Phaeozem towards Luvisol (kurgans K1 and K2), which is consistent with opinions regarding the transformations of chernozemic soils during the Holocene period [19,29,40,41]. Clear discrimination of the topsoil horizons of modern soils into non-overlapping classes referring to the land use and soil type has confirmed the potential of non-destructive spectroscopic methods in paleopedological studies.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This result suggests possible influences from the other physicochemical soil components important for pedogenic processes, such as carbonates and clay minerals [39]. However, the placement of some samples indicated the soil transformation (analyzed as the change from the bottom towards topsoil layers of the buried soil) from Chernozem through Phaeozem towards Luvisol (kurgan K3) and from Phaeozem towards Luvisol (kurgans K1 and K2), which is consistent with opinions regarding the transformations of chernozemic soils during the Holocene period [19,29,40,41]. Clear discrimination of the topsoil horizons of modern soils into non-overlapping classes referring to the land use and soil type has confirmed the potential of non-destructive spectroscopic methods in paleopedological studies.…”
Section: Discussionsupporting
confidence: 82%
“…The simple relationship of an origination of Chernozems and the presence of steppe vegetation and continental climate in Central Europe was recently questioned due to paleobotanic studies, which demonstrated the predominance of forest vegetation and strong human impacts during the Holocene. However, the other findings suggested that the early removal of forests and the expansion of pastures and arable lands since the Neolithic period could preserve or even restore some of these soils [28,29,36,37]. The determination of organic matter was successfully conducted by [19] in some buried Central European Chernozems using NIR spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil thickness was the highest in the depressed positions, and, on the contrary, the soil was the shallowest on the slopes with a more pronounced inclination, which are the initial manifestations of water erosion that, in this case, also lead to the mosaic-like discontinuity of the soil cover of original chernozems (Labaz et al 2019). In addition to the HC, ER was https://doi.org/10.17221/3/2024-SWR also at the monitored sites, and, simultaneously, Colluvisol was also identified in the accumulation zones.…”
Section: Resultsmentioning
confidence: 80%
“…On the basis of the analysis of the spatial distribution of the index of agricultural valorisation of production space in Poland, taking soil quality, agroclimate, relief, and water conditions into account [12,13], it was found that the farms in Banie and Swobnica have excellent conditions ( Figure 1). The decisive factor is constituted by soils, partially included in the so-called Pyrzyce black earths, which are among the most fertile in Poland [14,15]. The other two farms in the Gryfino district are characterized by very good conditions.…”
Section: Location and Characteristics Of The Studied Farmsmentioning
confidence: 99%